2011
DOI: 10.2109/jcersj2.119.238
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of antibodies on mesoporous silica materials and their binding abilities to antigens

Abstract: Mesoporous silicas (MPS) are potential materials for adsorption of antibodies on their surface as they have the following features: a) an ordered pore network and b) a high surface area. These unique features make MPS an excellent candidate as an immobilizing carrier for immunoassays. We present here the relationship between antibody molecules and pore diameters of various MPS; moreover, the thermal stability and the organic solvent stability of antibodies immobilized on MPS are evaluated. From six MPS, the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…These observations are consistent with earlier reports regarding the encapsulation of enzymes and antibodies in MSNPs. 50,75,76 ■. CONCLUSIONS We described the preparation of a new type of templated mesoporous silica nanoparticles (TA-MSNPs) with unique pore morphology, large pore volume, and narrow pore size distribution.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…These observations are consistent with earlier reports regarding the encapsulation of enzymes and antibodies in MSNPs. 50,75,76 ■. CONCLUSIONS We described the preparation of a new type of templated mesoporous silica nanoparticles (TA-MSNPs) with unique pore morphology, large pore volume, and narrow pore size distribution.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…The unique features, such as high surface area and large pore volume, make mesoporous silica an excellent candidate to be an immobilizing carrier for immunoassays. 7) Mesoporous silica is a potential material for the adsorption of antibodies. Endo et al reported formation of a thick coating of mesoporous silica powder on stainless steel by an electrophoretic deposition method.…”
Section: Mesoporous Materials By Self-assembly Of Surfactantsmentioning
confidence: 99%
“…Since enzymes are inactivated owing to structural changes triggered by solvent influences, prevention of conformational change in the limited space results in retention of activity. 22 When the size is matched between enzymes and nano-space, this effect is more pronounced. In case of MC, the size of FDH and pore diameter matches very well.…”
Section: Stability Of Fdh Against the Outer Environmentmentioning
confidence: 99%